2012
DOI: 10.3923/pjbs.2012.395.398
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Reverse Triangle Screw Fixation in Patients Suffering from Femoral Neck Fractures

Abstract: Although the fractures of femoral neck are not so common, their accompanying complications are more frequent and important. This research aims at studying the results of reverse triangle screw fixation in patients suffering from femoral neck fractures in two groups with perfect and imperfect position of the mentioned screw. In a cohort study, 51 patients with femoral neck fracture appointed for the so-called reverse triangle screw fixation were divided into two perfect and imperfect groups considering surgeon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…A total of 28 studies reported on both AVN incidence and the time interval between injury and surgery [ 16 , 17 , 22 , 25 , 27 , 28 , 29 , 30 , 32 , 33 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 49 , 51 , 52 , 54 , 55 , 56 , 57 , 59 , 65 , 67 ]. There was no significant correlation between AVN incidence weighted by sample size and time interval from injury to surgery, with a slope of weighted linear regression equal to −0.01 ( p = 0.843, R 2 = 0.01) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 28 studies reported on both AVN incidence and the time interval between injury and surgery [ 16 , 17 , 22 , 25 , 27 , 28 , 29 , 30 , 32 , 33 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 49 , 51 , 52 , 54 , 55 , 56 , 57 , 59 , 65 , 67 ]. There was no significant correlation between AVN incidence weighted by sample size and time interval from injury to surgery, with a slope of weighted linear regression equal to −0.01 ( p = 0.843, R 2 = 0.01) ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“… The relationship between AVN incidence and time from injury to surgery [ 16 , 17 , 22 , 25 , 27 , 28 , 29 , 30 , 32 , 33 , 36 , 40 , 41 , 42 , 43 , 44 , 45 , 47 , 49 , 51 , 52 , 54 , 55 , 56 , 57 , 59 , 65 , 67 ]. The size of the dot corresponds to the sample size of the study.…”
Section: Figurementioning
confidence: 99%